Heterointerface and tensile strain effects synergistically enhances overall water-splitting in Ru/RuO₂ aerogels - Sui, Nicole L. D. (2023)
Designing robust electrocatalysts for water-splitting is essential for sustainable hydrogen generation, yet difficult to accomplish. In this study, a fast and facile two-step technique to synthesize Ru/RuO2 aerogels for catalyzing overall water-splitting under alkaline conditions is reported. Benefiting from the synergistic combination of high porosity, heterointerface, and tensile strain effects, the Ru/RuO2 aerogel exhibits low overpotential for oxygen evolution reaction (189 mV) and hydrogen evolution reaction (34 mV) at 10 mA cm-2 , surpassing RuO2 (338 mV) and Pt/C (53 mV), respectively. Notably, when the Ru/RuO2 aerogels are applied at the anode and cathode, the resultant water-splitting cell reflected a low potential of 1.47 V at 10 mA cm-2 , exceeding the commercial Pt/C||RuO2 standard (1.63 V). X-ray adsorption spectroscopy and theoretical studies demonstrate that the heterointerface of Ru/RuO2 optimizes charge redistribution, which reduces the energy barriers for hydrogen and oxygen intermediates, thereby enhancing oxygen and hydrogen evolution reaction kinetics.